Cooling photovoltaic modules for power and efficiency enhancement - Al-Masalha, Ismail; Masuri, Siti Ujila; Badran, Omar O.; Aljamea, Dana M. Khadem; Alawin, Aiman Al; Abu-Rahmeh, Taiseer M.; Alkawaldeh, Naim Rizq (Praise Worthy Prize, 2024)
The main objective of this work is to reduce the temperature of the photovoltaic panel to increase its electrical efficiency. Water was used to achieve this goal by building a 5 cm high channel behind the photovoltaic panel so that the contact is direct between the solar panel and the water. The results were verified using indoor and outdoor testing and with numerical analysis as well. From the indoor experiments, it was found that uncooled modules got lower output power and electrical efficiency of 12.4 W and 4.13%, while for the cooling process, the higher values of 17.3 W and 5.69%, respectively were detected. In the outdoor experiments, the three photovoltaic modules were under the same weather conditions to ensure the validity of the comparisons. The output power and electrical efficiency without cooling were low and reached 21.36 W and 13.9%, respectively, while for cooling they reached higher values of 22.92 W and 14.5%, respectively.